Silver metal nanocluster and application thereof in electrocatalytic reduction of carbon dioxide

By using silver metal nanoclusters as catalysts, the problem of insufficient catalyst efficiency and selectivity in the existing electrocatalytic carbon dioxide reduction technology is solved, and catalytic performance is achieved with high efficiency, stable and excellent selectivity, which promotes the industrial application of electrocatalytic carbon dioxide reduction technology.

CN119566294AActive Publication Date: 2025-03-07ANHUI UNIV
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411830450.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-07
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

In the existing electrocatalytic carbon dioxide reduction technology, the catalyst efficiency and selectivity are insufficient, and the hydrogen evolution reaction competition is significant, making it difficult to achieve industrial application.

Method used

The nanoclusters containing 10 silver cores were used as catalysts to synthesize nanoclusters containing 10 silver cores and load them on carbon paper for electrocatalytic reduction of carbon dioxide.

Benefits of technology

It achieves efficient, stable and selective catalytic performance, reduces the reaction overpotential, improves the conversion efficiency, and maintains a long-term catalytic benefit in the electrocatalytic hydrogenation reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119566294A_ABST
    Figure CN119566294A_ABST
Patent Text Reader

Abstract

The invention discloses a silver metal nanocluster and application thereof in electrocatalytic reduction of carbon dioxide, and belongs to the technical field of electrocatalysis. The silver metal nanocluster is a nanocluster containing 10 silver cores, and the molecular formula of the silver metal nanocluster is Ag10 (SR) 6 (DPPP) 3 (CF3COO) 4. The silver metal nanocluster is loaded on carbon paper to obtain a loaded catalyst, and the loaded catalyst is used as a catalyst in the process of electrocatalytically reducing carbon dioxide into carbon monoxide. The method is simple, the synthesis condition is mild, the operation is simple, the catalytic performance is excellent, and the Faraday efficiency and the reaction selectivity are relatively high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrocatalysis, and in particular relates to a silver metal nanocluster and an application thereof in the electrocatalytic reduction of carbon dioxide. Background Art

[0002] With the intensification of global warming and energy crisis, the reduction and resource utilization of carbon dioxide (CO2) have become the focus of global attention. Electrochemical CO2 Reduction (ECO2R) technology is an emerging technology that uses electrical energy to convert carbon dioxide into high-value-added chemicals and fuels (such as carbon monoxide, methane, ethylene, etc.), which not only helps to alleviate carbon emissions, but also provides a new way for clean energy production. This technology is centered on the catalyst on the electrode surface, which activates stable carbon dioxide molecules and realizes their selective reduction through the transfer of electrons and protons. However, the carbon dioxide reduction process is complex, involving multi-step reaction pathways and multiple products, and its efficiency and selectivity are restricted by the performance of the catalyst. In addition, the competition of the hydrogen evolution reaction (HER) will also significantly reduce the Faraday efficiency, further increasing the difficulty of achieving industrialization. Therefore, the development of efficient, stable and highly selective catalysts, as well as the optimization of reaction conditions and electrochemical systems, are the core directions of current research in this field.

[0003] In recent years, important progress has been made in catalyst design and system optimization to address the challenges of electrocatalytic carbon dioxide reduction. For example, monometallic and bimetallic catalysts significantly improve the selectivity of target products by regulating electronic structure and surface geometry; nanostructured catalysts reduce reaction overpotential and improve conversion efficiency due to their high specific surface area and abundant active sites. In addition, heteroatom doping and surface functionalization technologies further optimize the performance of catalysts, while molecular catalysts have become a new research hotspot due to their highly tunable structure and high selectivity. At the same time, by improving the design of electrolytic cells, adjusting the pH value and temperature of the electrolyte, researchers have successfully reduced the impact of the hydrogen evolution reaction and improved the reaction efficiency. Looking to the future, electrocatalytic carbon dioxide reduction technology combined with renewable energy (such as solar and wind energy) is expected to achieve carbon neutrality and energy sustainable development goals, but it is still necessary to overcome technical bottlenecks through interdisciplinary collaborative research, find low-cost catalysts with high conversion and high selectivity in electrocatalytic hydrogenation reactions, and promote the transition from laboratory research to industrial application. Summary of the invention

[0004] In view of this, the present invention aims at the problems existing in the prior art and provides a silver metal nanocluster and its application in the electrocatalytic reduction of carbon dioxide. The present invention has mild synthesis conditions, simple operation, high yield of silver metal nanocluster and excellent catalytic performance.

[0005] The silver metal nanocluster of the present invention is a nanocluster containing 10 silver cores, and the molecular formula is Ag 10 (SR)6(DPPP)3(CF3COO)4, and there is a free CF3COO counter ion around the cluster structure.

[0006] The method for preparing silver metal nanoclusters of the present invention comprises the following steps:

[0007] Pour CF3COOAg (88 mg, 0.4 mmol) into a 100 mL round-bottom flask, add 20 mL of methanol, and stir on a magnetic stirrer until fully dissolved. Then add DPPP (41 mg, 0.1 mmol) to the above CF3COOAg methanol solution and stir again for about 10 minutes to fully dissolve it. At this time, the solution is colorless and transparent. Add adamantanethiol (Adm-SH, 34 mg, 0.2 mmol), and the colorless and transparent solution turns milky white. After 30 minutes, weigh 100 mg NaBH4 (2.64 mmol) and dissolve it in 5 mL of methanol, then quickly add it to the above mixture. The color of the solution gradually changes from milky white to brown-black. Continue the reaction at room temperature for 5 hours. After 5 hours, centrifuge the crude product at 10,000 rpm for 3 minutes to remove large particles that are insoluble in methanol during the reaction. The supernatant was dried using a rotary evaporator, and the crude product was repeatedly washed with a large amount of n-hexane, followed by extraction two to three times with dichloromethane solvent. The final purified product was dissolved with toluene and diffused with toluene / n-hexane solvent at room temperature, with a small amount of ethanol as a buffer layer. After about a week, transparent flaky crystals were obtained at the bottom of the single crystal bottle. In order to obtain higher quality single crystals, the flaky crystals were collected and recrystallized with dichloromethane.

[0008] The invention discloses an application of silver metal nanoclusters in electrocatalytic reduction of carbon dioxide.

[0009] The silver metal nanoclusters are loaded on carbon paper to obtain a loaded catalyst. The carbon paper electrode loaded with silver metal nanoclusters is used as a working electrode, and electrochemical reduction is performed using a reference electrode and a counter electrode; the reference electrode is an Ag / AgCl reference electrode; the counter electrode is a platinum sheet electrode. The electrochemical reduction is performed in an H-type three-electrode system electrolytic cell.

[0010] The cathode chamber electrolyte consists of alkaline electrolyte and water, and carbon dioxide needs to be passed for 30 minutes before testing to make the electrolyte reach saturation.

[0011] The alkaline electrolyte is one or more of potassium bicarbonate and potassium hydroxide, and the concentration of the alkaline electrolyte in the electrolyte is 0.5-1 mol / L.

[0012] The electrolyte in the anode chamber is an aqueous solution of an alkaline electrolyte. Preferably, the alkaline electrolyte is potassium bicarbonate.

[0013] During the catalytic hydrogenation reaction of electrocatalytic reduction of carbon dioxide to carbon monoxide, the reaction conditions may be conventional in the art.

[0014] Further, the voltage of the electrocatalytic hydrogenation reaction is -0.5V vs. RHE to -1.3V vs. RHE, preferably -0.7V vs. RHE to -1.3V vs. RHE. The time of the electrocatalytic hydrogenation reaction is 5 to 30 minutes, preferably 10 minutes. The temperature of the electrocatalytic hydrogenation reaction can be room temperature, for example, 20 to 25°C.

[0015] The supported catalyst is prepared by the following method:

[0016] Silver metal nanoclusters were dissolved in DMF, drop-coated on 1cm×2cm carbon paper, and dried. The cluster solution was configured with a concentration of 0.1-2mg / mL, and the content of 5 wt% nafion per mL was 20-50μL.

[0017] More preferably, the cluster solution is prepared at 2 mg / mL, and the content of 5 wt % nafion per mL is 40 μL.

[0018] The carbon paper is commercially available in the art. The technical parameters of the carbon paper are as follows: resistivity 5.5 mΩ.cm 2 , density 0.83g / cm 3 , thickness 0.21 mm ± 0.01 mm; for example, HCP 120 series. The size of the carbon paper can be cut according to experimental needs, for example, (1 cm × 1 cm) to (3 cm × 3 cm), preferably 1 cm × 2 cm.

[0019] Compared with the prior art, the beneficial effects of the present invention include:

[0020] 1. The preparation method of silver metal nanoclusters provided by the present invention has mild synthesis conditions, simple and controllable operation, high yield, easy to repeat and scale up, and is suitable for mass production.

[0021] 2. The silver metal nanoclusters prepared by the present invention are small in size, high in stability, and good in catalytic performance, providing broad prospects for their subsequent applications.

[0022] 3. The silver metal nanocluster catalyst prepared by the present invention has low cost and good conversion rate and selectivity in the electrocatalytic hydrogenation reaction.

[0023] 4. In a preferred embodiment of the present application, the silver metal nanocluster catalyst of the present application can maintain a high catalytic efficiency and high stability in the electrocatalytic hydrogenation reaction after a single group is cycled 10 times. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the UV spectrum of silver metal nanoclusters.

[0025] Figure 2 Mass spectrum of silver metal nanoclusters.

[0026] Figure 3 Single crystal structure diagram of silver metal nanoclusters (Ag: blue; S: red; P: purple).

[0027] Figure 4 This is the thermogravimetric analysis diagram of silver metal nanoclusters.

[0028] Figure 5 Transmission electron microscope (TEM) images of the silver metal nanocluster catalysts of Examples 2 and 3 before and after the reaction.

[0029] Figure 6 The linear sweep voltammetry (LSV) curves of Example 3 and Comparative Example 1 in the electrochemical reduction reaction are shown in FIG.

[0030] Figure 7 This is a comparison chart of the catalytic results of electro-reduction of different catalysts in Example 4 and Control Example 2 at a voltage of -0.8 V vs. RHE.

[0031] Figure 8 This is a diagram showing the catalytic results of the electro-reduction of the silver metal nanocluster catalyst of Example 4 at different potentials.

[0032] Fig. 9 This is a gas phase detection diagram of the electro-reduction of carbon dioxide products by the silver metal nanocluster catalyst of Example 4.

[0033] Fig.10 This is a stability test diagram of the silver metal nanocluster catalyst of Example 5. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0035] The experimental methods in the present invention are conventional methods unless otherwise specified. The experimental materials used in the present invention are purchased from the market unless otherwise specified.

[0036] Example 1: Preparation of silver metal nanoclusters

[0037] The method for preparing silver metal nanoclusters comprises the following steps:

[0038] Pour CF3COOAg (88 mg, 0.4 mmol) into a 100 mL round-bottom flask, add 20 mL of methanol, and stir on a magnetic stirrer until fully dissolved. Then add DPPP (41 mg, 0.1 mmol) to the above CF3COOAg methanol solution and stir again for about 10 minutes to fully dissolve it. At this time, the solution is colorless and transparent. Add adamantanethiol (Adm-SH, 34 mg, 0.2 mmol), and the colorless and transparent solution turns milky white. After 30 minutes, weigh 100 mg NaBH4 (2.64 mmol) and dissolve it in 5 mL of methanol, then quickly add it to the above mixture. The color of the solution gradually changes from milky white to brown-black. Continue the reaction at room temperature for 5 hours. After 5 hours, centrifuge the crude product at 10,000 rpm for 3 minutes to remove large particles that are insoluble in methanol during the reaction. The supernatant was dried by rotary evaporation, and the crude product was repeatedly washed with a large amount of n-hexane, and then extracted with dichloromethane solvent for two to three times. The purified product was dissolved in toluene for the last time, and diffused with toluene / n-hexane solvent at room temperature, with a small amount of ethanol as a buffer layer. After about a week, transparent flake crystals were obtained at the bottom of the single crystal bottle. In order to obtain higher quality single crystals, the flake crystals were collected and recrystallized with dichloromethane. The UV spectrum is as follows Figure 1 As shown in the mass spectrum Figure 2 As shown, the single crystal structure is shown in Figure 3 As shown in the thermogravimetric analysis, Figure 4 shown.

[0039] Example 2: Preparation of Silver Metal Nanocluster Catalyst

[0040] The carbon paper was cut into small pieces of 1 cm×2 cm, 2 mg of silver metal nanoclusters were dissolved in 1 ml of DMF containing 40 μl of 5 wt% nafion, and the mixture was drop-coated on the carbon paper with a drop-coating area of ​​1 cm×1 cm, and then dried for later use.

[0041] Example 3: Electroreduction performance test of silver metal nanocluster catalyst

[0042] The test was conducted using a Chenhua 760 electrochemical workstation under a standard three-electrode system. The silver metal nanocluster catalyst prepared in Example 2 was used as the working electrode, Ag / AgCl as the reference electrode, and a platinum sheet as the counter electrode. The reaction was carried out using an H-type electrolytic cell, and the chambers were separated by a DuPont 117 cation exchange membrane. The electrolyte in the anode chamber was a 0.5 mol / L potassium bicarbonate solution, and the cathode chamber was a 0.5 mol / L potassium bicarbonate solution and passed for 30 minutes to saturate the carbon dioxide.

[0043] The parameters are set as follows: initial potential 0.2V vs. RHE, end potential -1.3V vs. RHE, sweep rate -0.1mV / s. The results are as follows: Figure 6 As shown. The clusters are dispersed evenly on the carbon paper carrier before and after electrolysis, and no agglomeration is found. Figure 5 shown.

[0044] Example 4: Detection of Carbon Dioxide Electroreduction Using Silver Metal Nanocluster Catalysts

[0045] The test was conducted using a Chenhua 760 electrochemical workstation under a standard three-electrode system. The silver metal nanocluster catalyst prepared in Example 2 was used as the working electrode, Ag / AgCl as the reference electrode, and a platinum sheet as the counter electrode. The reaction was carried out using an H-type electrolytic cell, and the chambers were separated by a DuPont 117 cation exchange membrane. The electrolyte in the anode chamber was a 0.5 mol / L potassium bicarbonate solution, and the cathode chamber was a 0.5 mol / L potassium bicarbonate solution and passed for 30 minutes to saturate the carbon dioxide.

[0046] The catalytic effects obtained after 10 minutes of electrocatalytic hydrogenation at -0.7, -0.8, -0.9, -1, -1.1, -1.2 and -1.3 V vs. RHE are shown in the figure. Figure 8 It can be seen that at -0.8V vs.RHE, carbon monoxide reaches a maximum Faraday efficiency of 94.8%, and maintains a Faraday efficiency of more than 90% in a wide potential range of -0.8V vs.RHE ~ -1.1V vs.RHE. As the potential gradually increases, the Faraday efficiency of carbon monoxide decreases slightly but still remains above 80%. The gas phase products are detected by gas chromatography, such as Fig. 9 shown.

[0047] Example 5: Cyclic stability test of carbon dioxide electroreduction of silver metal nanocluster catalyst

[0048] The test was conducted using a Chenhua 760 electrochemical workstation under a standard three-electrode system. The silver metal nanocluster catalyst prepared in Example 2 was used as the working electrode, Ag / AgCl as the reference electrode, and a platinum sheet as the counter electrode. The reaction was carried out using an H-type electrolytic cell, and the chambers were separated by a DuPont 117 cation exchange membrane. The electrolyte in the anode chamber was a 0.5 mol / L potassium bicarbonate solution, and the cathode chamber was a 0.5 mol / L potassium bicarbonate solution and passed for 30 minutes to saturate the carbon dioxide.

[0049] The experimental conditions were the same as the best selectivity conditions in Example 4. The same working electrode was used to conduct ten experiments to ensure that the experimental conditions were the same each time. At the end of each experiment, the electrolytic cell was cleaned to ensure that no product remained. The experimental results are shown in Figure 1. Fig.10 As shown, the Faraday efficiency of carbon monoxide remains basically unchanged and the catalyst is relatively stable.

[0050] Comparative Example 1: Preparation of Carbon Paper Catalyst

[0051] Cut the carbon paper into small pieces of 1cm×2cm for later use.

[0052] Comparative Example 2: Electrochemical Reduction of Carbon Dioxide Detection Using Carbon Paper Catalyst

[0053] The test was conducted using a Chenhua 760 electrochemical workstation under a standard three-electrode system. The carbon paper catalyst prepared in Control Example 1 was used as the working electrode, Ag / AgCl as the reference electrode, and a platinum sheet as the counter electrode. The reaction was carried out using an H-type electrolytic cell, and the chambers were separated by a DuPont 117 cation exchange membrane. The electrolyte in the anode chamber was a 0.5 mol / L potassium bicarbonate solution, and the cathode chamber was a 0.5 mol / L potassium bicarbonate solution and passed for 30 minutes to saturate the carbon dioxide.

[0054] The LSV test was carried out under the optimal conditions of Example 3, and the results were as follows Figure 6 shown.

[0055] The results obtained after 10 minutes of electrocatalytic hydrogenation under the optimal conditions of Example 3 are as follows: Figure 7 As shown. Figure 7 It can be seen that at -0.8 V vs. RHE, the catalytic efficiency of the carbon paper catalyst is low, and the Faraday efficiency of carbon monoxide is only 4.5%.

[0056] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A silver metal nanocluster, characterized in that: The silver metal nanocluster is a nanocluster containing 10 silver cores, and the molecular formula is Ag 10 (SR)6(DPPP)3(CF3COO)4.

2. Use of the silver metal nanoclusters according to claim 1 in the electrocatalytic reduction of carbon dioxide.

3. The use according to claim 2, characterized in that: A carbon paper electrode loaded with silver metal nanoclusters is used as a working electrode, and an electrochemical reduction is performed using a reference electrode and a counter electrode; the reference electrode is an Ag / AgCl reference electrode; and the counter electrode is a platinum sheet electrode.

4. The use according to claim 3, characterized in that: Silver metal nanoclusters are dissolved in DMF to prepare a cluster solution with a concentration of 0.1-2 mg / mL, wherein the content of 5 wt% nafion per milliliter in the cluster solution is 20-50 μL; the mixed solution is drop-coated on 1 cm×2 cm carbon paper and dried to serve as a working electrode.

5. The use according to claim 4, characterized in that: A cluster solution with a concentration of 2 mg / mL was prepared, wherein the content of 5 wt% nafion per mL in the cluster solution was 40 μL.

6. The use according to claim 4, characterized in that: The technical parameters of the carbon paper are: resistivity 5.5 mΩ.cm 2 , density 0.83g / cm 3 , thickness 0.21mm±0.01mm.

7. The use according to claim 3, characterized in that: The voltage of the electrocatalytic hydrogenation reaction is -0.5V vs. RHE to -1.3V vs. RHE, and the reaction time is 5 to 30 minutes.

8. The use according to claim 7, characterized in that: The voltage of the electrocatalytic hydrogenation reaction was -0.7 V vs. RHE to -1.3 V vs. RHE, and the reaction time was 10 min.

9. The use according to claim 3, characterized in that: The electrolyte in the cathode chamber is composed of an alkaline electrolyte and water, into which carbon dioxide is introduced before the reaction to make it reach a saturated state; the electrolyte in the anode chamber is an aqueous solution of an alkaline electrolyte.

Citation Information

Patent Citations

  • Mold-prevention coating cable and preparation method thereof

    CN106653200A

  • Fluorescence color-change material capable of directionally identifying dichloromethane, trichloromethane and tetrachloromethane and preparation method of fluorescence color-change material

    CN108165256A

  • Metal nanocluster structure optimization method

    CN111326217A

  • Accurate metal cluster-based composite catalyst as well as preparation method and application thereof

    CN114588896A

  • 1, 3-bis (diphenylphosphine) propane-based fifteen-core sulfur silver cluster compound as well as preparation method and application thereof

    CN114957328A